2016
DOI: 10.1007/s12272-016-0880-z
|View full text |Cite
|
Sign up to set email alerts
|

RSK2 and its binding partners in cell proliferation, transformation and cancer development

Abstract: RSK2 is a serine/threonine kinase and a member of the p90 ribosomal S6 kinase (p90; RSKs) family, which regulates cell proliferation and transformation induced by tumor promoters such as epithelial growth factor (EGF), 12-O-tetradecanoylphorbol-13-acetate (TPA), and ultraviolet (UV) radiation. RSKs respond to many growth factors, hormones, neurotransmitters and environmental stresses. In signaling cascades, RSK2 is regulated under the control of extracellular signal-regulated kinase 1 (ERK1) and 2 (ERK2) activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 96 publications
0
31
0
Order By: Relevance
“…To explore the anticancer activity of magnolin, we utilized several cancer cells including pancreatic cancer cells (AsPC‐1, BxPC‐3, Capan‐1, Capan‐2, and MIA PaCa‐2), colon cancer cells (SW480, HCT 116, HT‐29, and COLO 205), breast cancer cells (MCF7, MDA‐MB‐231, SKBR3, and BT‐474), and ovarian cancer cells (TOV‐112D and SKOV3). Since it has been reported that cancer cells originating from different organs or tissues harbor predominately different mutation(s) in different genes, we firstly analyzed mutations of oncogenes and tumor suppressor genes against the aforementioned cancer cell lines by searching the CCLE (https://portals.broadinstitute.org/ccle_legacy/home) mutaome database (Table ). The results showed that pancreatic cancer cells exhibited gain‐of‐function mutations, mainly in MAPK, and loss‐of‐function mutations, mainly in p16, p53, and SMAD4 (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…To explore the anticancer activity of magnolin, we utilized several cancer cells including pancreatic cancer cells (AsPC‐1, BxPC‐3, Capan‐1, Capan‐2, and MIA PaCa‐2), colon cancer cells (SW480, HCT 116, HT‐29, and COLO 205), breast cancer cells (MCF7, MDA‐MB‐231, SKBR3, and BT‐474), and ovarian cancer cells (TOV‐112D and SKOV3). Since it has been reported that cancer cells originating from different organs or tissues harbor predominately different mutation(s) in different genes, we firstly analyzed mutations of oncogenes and tumor suppressor genes against the aforementioned cancer cell lines by searching the CCLE (https://portals.broadinstitute.org/ccle_legacy/home) mutaome database (Table ). The results showed that pancreatic cancer cells exhibited gain‐of‐function mutations, mainly in MAPK, and loss‐of‐function mutations, mainly in p16, p53, and SMAD4 (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The RSK (90 kDa ribosomal S6 kinase) family comprises a group of highly related serine/threonine kinases that regulate diverse cellular processes, including cell growth, proliferation, survival and motility . Members of this family, which are downstream effectors of the Ras/ERK signaling pathway, includes four vertebrate isoforms (RSK1, RSK2, RSK3, and RSK4) . RSK2 was identified as an important effector of ERK in global transcriptional regulation.…”
Section: Discussionmentioning
confidence: 99%
“…[12] Members of this family, which are downstream effectors of the Ras/ERK signaling pathway, includes four vertebrate isoforms (RSK1, RSK2, RSK3, and RSK4). [13] RSK2 was identified as an important effector of ERK in global transcriptional regulation. Indeed, activated RSK2 was shown to phosphorylate several transcription factors including AP-1, CREB, c-Fos, c-Jun, and others, some of which contribute to the IEG (immediate-early gene) response or are IEG products themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Our published studies identified a role for integrins in the regulation of abscission (14) and have defined a role for ERK and its downstream target the ribosomal S6 kinase (RSK) (14). RSKs are a family of serine/threonine kinases that phosphorylate many cytoplasmic and nuclear targets (15)(16)(17). We previously demonstrated that depletion of either RSK1 or RSK2 in mammary epithelial cells inhibited cytokinesis (14), but did not determine whether both RSK isoforms were activated downstream of integrins or whether RSK1 and RSK2 regulated cytokinesis by similar or distinct mechanisms.…”
Section: Introductionmentioning
confidence: 99%